SISTEM APPRAISAL PADA TEKS IKLAN KOMERSIAL DI TABLOID NOVA - Yunita Nugraheni (PAROLE: Journal of Linguistics and Education, 2011)
This research is aimed to identify the appraisal properties in the text of commercial advertisement in Nova tabloid. There are 17 texts of commercial advertisement as the samples of data of research, which were obtained by purposive sampling method. Those texts have been analysed by appraisal system theory stated by White (1998). The appraisal system focuses on the assessment and evaluation of attitude (affect, judgment and appreciation), amplifying attitude and the source of attitude (graduation). The result showed that the positive appreciation dominates the assessment of attitude on the commercial advertisement texts. The manufacturers gave the positive attitude to the product and service being advertised in Nova tabloid because they want to persuade and suggest that the consumers buy and use their products